The Nature of Administration and Supervision as Elements in Developing Educational Resources - Nugraha, Hendika Adi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Educational administration and supervision are two fundamental, interrelated aspects of educational resource development. Administration functions as a manager who plans, organizes, and oversees the efficient use of resources, while supervision plays a role in improving the quality of teaching and teacher performance through constructive guidance and evaluation. This study aims to identify the nature of administration and supervision and their roles in developing the professionalism of educators and improving the quality of education. Through a literature review, it was found that collaboration between effective administration and targeted supervision creates a conducive learning environment, supports the growth of teacher competencies, and contributes to the achievement of the educational vision. The results of the study indicate that administration and supervision are two important elements that serve as the main foundation in educational resource development. Administration provides a structure and governance that regulates resource allocation, planning, and organization that ensures the continuity of the educational process efficiently and in alignment with the school's vision. Supervision, on the other hand, plays a role in providing guidance, evaluation, and motivation for educators to continuously improve their competence and teaching quality. The synergy between administration and supervision not only supports the professional development of teachers and other educational staff but also creates a conducive learning environment and improves the overall quality of educational services. With structured administration and effective supervision, schools are able to achieve higher educational standards, meet community expectations, and contribute to the formation of a more qualified generation